Chest X-ray Pneumonia Classification using AlexNet - Jamil, Hafizudin; Mohamed, Masnani; Joret, Ariffuddin (Evolution in Electrical and Electronic Engineering, 2021)
Pneumonia is caused by infected alveoli inside the human lungs, if the tissue inside the human lungs has inflammation, it may occur pus inside it. In order to detect that a patient has pneumonia, a medical professional has to diagnose their chest X-ray and do physical exams towards the patient. Nowadays, deep learning has been widely used in a lot of industries that have helped a lot of humans to speed up their work. Therefore, this project aims to determine the chest X-ray that is affected by pneumonia. In order to determine the result, a Convolutional Neural Network (CNN) was used with architecture design of AlexNet. The result obtained was more than 95% which is very good in terms of its accuracy in detecting disease.